Pengaruh Likuiditas, Profitabilitas dan Sales Growth dalam Memprediksi Financial Distress (Progress, 2024)
This research aims to determine whether there is a significant influence between liquidity with the current ratio proxy, profitability with the Return On Assets proxy, and sales growth in predicting Financial Distress in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2021. The data collection technique for this research was obtained using documentation and library study methods. The documentation method was carried out by collecting and studying documents such as data and reports, while the library study method was by collecting data related to research through book or literature references. This research uses data analysis in the form of: descriptive analysis, statistical analysis (multiple correlation analysis, multiple linear regression, coefficient of determination, T test, and F test. Based on the author's research, finally the results obtained were 97% of the three independent variables, namely liquidity, profitability and sales growth, which could explain financial distress. Meanwhile, the remaining 3% is influenced by variables not examined in this research, such as the company's growth rate, sales stability, operating leverage, owner and management attitudes.